Outsourcing Labor Within the Legal Framework of Employment Relations - Hutagalung, Henrico DP; Muhammad Arifin; Ida Hanifah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Positive impacts of national development progress include the growth and development of economic activity centers, resulting in the establishment of new industrial centers and providing employment opportunities for the community. The legal framework for employment relations between outsourced workers and parties in the labor sector is regulated by Pancasila Industrial Relations (hereinafter abbreviated as HIP). HIP is an industrial relationship based on the manifestation of all the principles of Pancasila and the 1945 Constitution (hereinafter abbreviated as UUD 1945), and develops in accordance with the character of the Indonesian nation. Meanwhile, industrial relations refers to all types of employment relationships between employers and employees, both at the regional and national company levels, relating to socio-economic matters such as wages, working hours, working conditions, employment relations, and so on. Employment relations serve as a basis for parties to protect their respective interests and avoid discriminatory practices and human rights violations during the organizational process to achieve company goals. Outsourced labor practices related to employment relations are frequently discussed and debated among various groups. This is directly related to companies' efforts to reduce costs related to human resource utilization and their responsibility to provide legal protection for workers in the employment relationship. The employment relationship between workers and companies in outsourcing practices must reflect legal protection for workers, as stated in the Preamble to the 1945 Constitution: to protect the entire Indonesian nation and its entire homeland and to advance general welfare based on Pancasila to achieve social justice for all Indonesians. Although outsourcing is limited to specific fields, it is widespread in companies' core businesses. Therefore, the government's role is crucial in ensuring that workers' rights within an employment relationship are fulfilled in accordance with applicable laws.